Integrase strand transfer inhibitors in the management of HIV-positive individuals. (May 2014) - Mesplède, Thibault; Quashie, Peter K.; Zanichelli, Veronica; Wainberg, Mark A.
Abstract: The use of highly active antiretroviral therapy against human immunodeficiency virus (HIV) can lead to rare instances of treatment failure and the emergence of drug resistance. HIV drug-resistant strains are archived in cellular reservoirs, and this can exclude the future efficacy of drugs or drug classes against which resistance has emerged. In addition, drug-resistant viruses can be transmitted between individuals. HIV drug resistance has been countered through the constant development of new antiretroviral drugs. Integrase strand transfer inhibitors, that actively block the integration of the HIV genome into the host DNA, represent the most recent antiretroviral drugs. Of these, raltegravir, elvitegravir, and dolutegravir are the only integrase strand transfer inhibitors that have been approved for human therapy by the US Food and Drug Administration. Dolutegravir is unique in its ability to seemingly evade HIV drug resistance in treatment-naïve individuals. Here, we review the use of integrase strand transfer inhibitors in the management of HIV, focusing on HIV resistance.